2019
DOI: 10.1177/0081246319892898
|View full text |Cite
|
Sign up to set email alerts
|

The cost of caring: secondary traumatic stress and burnout among lay trauma counsellors in the Western Cape Province

Abstract: The psychological and emotional risks associated with providing care to traumatized populations have been largely overlooked in the literature on non-professional trauma counselling in South Africa. Non-professional or lay trauma counsellors are frontline service providers and typically the first point of contact for people in community contexts who have experienced traumatic events. The main aim of this study was to investigate the professional quality of life including compassion satisfaction, secondary trau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 43 publications
1
11
0
Order By: Relevance
“…A study showed high prevalence of vicarious traumatization among social workers after 20 months of terrorist attack on World Trade Centre 5 . Similar results were found for humanitarian aid workers in India and 8% of them met the criteria of PTSD 6 . Many other studies have been carried out with therapists, counselors, social workers and nurses with similar findings 7 .…”
Section: Original Articlesupporting
confidence: 80%
“…A study showed high prevalence of vicarious traumatization among social workers after 20 months of terrorist attack on World Trade Centre 5 . Similar results were found for humanitarian aid workers in India and 8% of them met the criteria of PTSD 6 . Many other studies have been carried out with therapists, counselors, social workers and nurses with similar findings 7 .…”
Section: Original Articlesupporting
confidence: 80%
“…For each subscale, a score above 42 is considered high, 23–41 average, and 22 or less is considered low [ 46 ]. The ProQOL scale has been widely used, including in multiple studies in healthcare settings in South Africa [ 49 52 ].…”
Section: Methodsmentioning
confidence: 99%
“…The prevalence of mental health disorders in the country is higher compared with other African countries (Benjet et al, 2016; Padmanabhanunni, 2018). This burden of mental illness is further aggravated by a low ratio of professional mental health care providers to the population (e.g., 2.5 psychologists per 100 000 of the population) and limited access to psychological services particularly in low-income communities (Padmanabhanunni, 2019). To address the demand for counseling services and fill an essential gap in the provision of psychological care to vulnerable populations, the services provided by nonprofessional or lay counselors have been utilized for several decades in South Africa.…”
mentioning
confidence: 99%